Who Talks to Whom? Intra- and Interdisciplinary Communication of Economics Journals - Pieters, Rik; Baumgartner, Hans (Journal of Economic Literature, 2002)
Citation patterns between 42 journals in economics from 1995 to 1997 are examined, plus between economics and anthropology, political science, psychology, sociology and five business disciplines. Building on social network theory, we identify a hierarchical organization of journals in economics and seven journal clusters. Major citation flows are found from all areas of economics to the general interest and theory and method clusters, but not the other way around. Economics emerges as a significant source of interdisciplinary knowledge for the other social sciences and business. However, no area of economics appears to build substantially on insights from its sister disciplines.